Optical Design with Narrow-Band Imaging for a Capsule Endoscope. (10th January 2018) - Yen, Chih-Ta; Lai, Zong-Wei; Lin, Yu-Ting; Cheng, Hsu-Chih
Abstract : The study proposes narrow-band imaging (NBI) lens design of 415 nm and 540 nm of a capsule endoscope (CE). The researches show that in terms of the rate of accuracy in detecting and screening neoplastic and nonneoplastic intestinal lesions, the NBI system outperformed that of traditional endoscopes and rivaled that of chromoendoscopes. In the proposed NBI CE optical system, the simulation result shows the field of view (FOV) was 109.8°; the modulation transfer function (MTF) could achieve 12.5% at 285 lp/mm and 34.1% at 144 lp/mm. The relative illumination reaches more than 60%, and the system total length was less than 4 mm. Finally, this design provides high-quality images for a 300-megapixel 1/4 ″ CMOS image sensor with a pixel size of 1.75 μ m.